Trends of sphincter-preserving surgeries for low lying rectal cancer: A 20-year experience in China - Zheng, Kuo; Hu, Qingqing; Yu, Guanyu; Zhou, Leqi; Yao, Yuting; Zhou, Yuan; Wang, Hao; Hao, Liqiang; Yu, Enda; Lou, Zheng; Zhang, Yongjing; Qiu, Hong; et al. (Frontiers in Oncology, 2022)
Background: Over the last 2 decades, patients with low rectal cancer have had better outcomes from improvements in surgical techniques in sphincter preservation. We aimed to quantify the trends in sphincter-preserving surgeries for low rectal cancer over 20 years in a top tertiary hospital in China. Methods: Between 1999 and 2021, a cohort of patients with primary malignant rectal tumor ≤5cm from the anal verge and who received selective surgery at Changhai Hospital, Shanghai, China, was identified. Data were extracted from electronic medical records. A Joinpoint Regression Model was used to analyze trends in surgical procedures by average annual percentage change (AAPC). Adjusted Cox proportional hazards regression model was used to assess overall survival. Results: Among a total of 4,172 patients during the study period, 3,111 (74.6%) underwent a sphincter-preserving surgery and 1,061 (25.4%) received APR. Sphincter-preserving surgery increased 3.6% per year (95%CI, 2.3-4.9). Anterior resection was the most performed procedure (86.3%) and maintained a steady trend, while intersphincteric resection increased 49.4% annually (95%CI, 19.5-86.7) after initiation. Laparoscopic techniques increased 15.1% per year (95%CI, 8.4-43.4) after initiation. Sphincter-preserving surgery increased annually for tumors ≤2cm, 2-≤3cm and 3-≤4cm from the anal verge (AAPC 7.1, 4.5-9.8; 4.7, 3.1-6.3; 2.7, 1.7-3.6, respectively). Furthermore, patients with sphincter-preserving surgery had a lower risk of death compared to abdominoperineal resection (APR) (adjusted HR 0.78, 95% CI, 0.65-0.93, p=.01). Conclusions: Utilization of sphincter-preserving surgeries increased significantly over the last 20 years. Patients with low rectal cancer who underwent sphincter preservation had better survival than similar patients who underwent APR.